The Semantics of Polysemy : Reading Meaning in English and Warlpiri. - Riemer, Nick (Cognitive Linguistics Research CLR., 2005)
This book, addressed primarily to students and researchers in semantics, cognitive linguistics, English, and Australian languages, is a comparative study of the polysemy patterns displayed by percussion/impact ('hitting') verbs in English and Warlpiri (Pa.